Characterization of Polysaccharide A Response Reveals Interferon Responsive Gene Signature and Immunomodulatory Marker Expression - Alvarez, Carlos A.; Jones, Mark B.; Hambor, John; Cobb, Brian A. (Frontiers in Immunology, 2020)
Polysaccharide A (PSA), a capsular carbohydrate from the commensal gut bacteria Bacteroides fragilis, has been shown to possess both potent T cell-dependent pro- and anti-inflammatory properties. PSA is able to induce abscess and adhesion formation in sepsis models, but can also inhibit asthma, inflammatory bowel disease (IBD) and experimental autoimmune encephalomyelitis (EAE) through MHCII-dependent activation of CD4+ T cells. Yet, despite decades of study, the ability of PSA to balance both these pro- and anti-inflammatory responses remains poorly understood. Here we utilized an unbiased systems immunology approach consisting of RNAseq transcriptomics, high-throughput flow cytometry and Luminex analysis to characterize the full impact of PSA-mediated stimulation of CD4+ T cells. We found that exposure to PSA resulted in the upregulation and secretion of IFNγ, TNFα, IL-6 and CXCL10, consistent with an interferon responsive gene (IRG) signature. Importantly, PSA stimulation also led to expression of immune checkpoint markers Lag3, Tim3 and especially PD1, which were also enriched and sustained in the gut associated lymphoid tissue of PSA-exposed mice. Taken together, PSA responding cells display an unusual mixture of pro-inflammatory cytokines and anti-inflammatory surface receptors, consistent with the ability to both cause and inhibit inflammatory disease.